Dasatinib treatment of imatinib-resistant and imatinib-intolerant patients with chronic myeloid leukemia in a chronic phase - Ol'ga Yur'evna Vinogradova (Терапевтический архив, 2009)
Aim. To analyse resistance to imatinib therapy, efficacy and safety of dasatinib. Material and methods. A total of 18 patients with chronic myeloid leukemia (CML) in a chronic stage received dasatinib for 9-30 months (median 30 months) to September 2008. Results. Lethal outcomes during dasatinib treatment were absent. To September 2008, 16(89%) patients were alive, 2(11%) patients died of the disease progression after dasatinib discontinuation. A complete clinicohematological response was observed in all the patients. Major cytogenetic, complete cytogenetic, major molecular, complete molecular responses were achieved in 12(67%), 10(55%), 7(39%) and 5(28%) patients, respectively. Hematological and non-hematological toxicity occurred in 9(50%) patients. Now 12(67%) patients continue dasatinib treatment, in 6(33%) patients the drug was discontinued. Conclusion. The results from trials in Russian Hematological Research Center are the same as in the international study. Dasatinib is effective and well tolerated therapeutic option for imatinib-resistant patients with a chronic phase of CML.